2010
DOI: 10.1016/j.rpor.2010.08.003
|View full text |Cite
|
Sign up to set email alerts
|

A review on photoneutrons characteristics in radiation therapy with high-energy photon beams

Abstract: In radiation therapy with high-energy photon beams (E > 10 MeV) neutrons are generated mainly in linacs head thorough (γ,n) interactions of photons with nuclei of high atomic number materials that constitute the linac head and the beam collimation system. These neutrons affect the shielding requirements in radiation therapy rooms and also increase the out-of-field radiation dose of patients undergoing radiation therapy with high-energy photon beams. In the current review, the authors describe the factors influ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
51
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 106 publications
(61 citation statements)
references
References 50 publications
(84 reference statements)
0
51
0
Order By: Relevance
“…However, we preferred to use mSv/MU, since it would be more meaningful to compare open and wedged fields for the same irradiation time. The rationale behind our idea was that the use of wedge filter decreases the photon fluence reaching the d max due to photon attenuation in the wedge, and a new factor known as wedge factor must be applied to yield same dose with open field at defined depth or d max as cited by Naseri et al [3],. Consequently, the total irradiation time or beam on time increase with wedge filters.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, we preferred to use mSv/MU, since it would be more meaningful to compare open and wedged fields for the same irradiation time. The rationale behind our idea was that the use of wedge filter decreases the photon fluence reaching the d max due to photon attenuation in the wedge, and a new factor known as wedge factor must be applied to yield same dose with open field at defined depth or d max as cited by Naseri et al [3],. Consequently, the total irradiation time or beam on time increase with wedge filters.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, the contribution of photo-neutron dose was investigated using Monte Carlo (MC) simulation and various dosimetric measurement techniques. A review of the literature reported that the majority of the studies consisted of MC simulations, and supplementary dosimetric studies are required to evaluate the consistency of MC calculations [3].…”
Section: Introductionmentioning
confidence: 99%
“…The essential part of photoneutrons produced in radiation therapy with highenergy photons originates from the linac head, where a considerable amount of (gamma, n) interactions occur between high-energy photons produced in the target and high Z materials found in the linac head. A recent review on photoneutron characteristics in radiation therapy has been published and is recommended for further detailed information [4]. Neutrons with higher radiobiological effectiveness or weighting factors up to 20 relative to photon beams increase unwanted whole-body radiation doses to the staff and patient, and consequently increase the probability of harmful effects such as cancers [5].…”
Section: Introductionmentioning
confidence: 99%
“…Electronic devices in the treatment room are also adversely affected by the production of photoneutrons [9,10]. All of the materials found in the LINAC room are capable of doing neutron absorption reactions [11].…”
Section: Introductionmentioning
confidence: 99%